Comparison of Value Perceptions of French and Turkish Secondary School Students - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2019)
In the present study, the aim was to compare the value perceptions of the 7th and 8th grade students of the French and Turkish schools. The study was designed in line with the phenomenology, which is one of the qualitative research methods; and the students were determined according to the criterion sampling method, which is one of the purposeful sampling methods. The data that were obtained in the study were analyzed with the descriptive analysis technique. According to the results of the study, the students of both schools explained the value concept as the care given for something, cost and worth, which were similar in both schools. About this explanation, the students of the French school stated values that were more various. The students of both schools frequently mentioned universalism-concern, and the students of the Turkish school rarely mentioned power-dominance; and the students of the French school stated that people should have values in universalism-nature categories. In priority of values and in universal value perceptions, the students of both schools stated many similar and different values.
Keywords: Value; Values education; France; Turkey; Comparative education